Guyana : Enhanced Initiative for Heavily Indebted Poor Countries Completion Point Document. (IMF Staff Country Reports; Country Report ;, 2004)
This paper reviews Guyana's progress under the Enhanced Initiative for Heavily Indebted Poor Countries (HIPC). The staff of the IMF and IDA considers that Guyana's performance with respect to the conditions for reaching the completion point under the enhanced HIPC Initiative has been satisfactory. The authorities were able to establish a track record of satisfactory policy implementation under the Poverty Reduction and Growth Facility (PRGF)-supported program, evidenced by the completion of the first program review in early September and good progress toward meeting the conditions of the second review due in February 2004.